2017
DOI: 10.1080/03601234.2017.1261538
|View full text |Cite
|
Sign up to set email alerts
|

Lead, cadmium and mercury contents and bioaccumulation potential of wild edible saprophytic and ectomycorrhizal mushrooms, Croatia

Abstract: Lead (Pb), cadmium (Cd), and mercury (Hg) contents in ten species of edible mushrooms in Trakošćan, Croatia were determined. In addition, the similarity between the studied species was determined by cluster analysis. The caps and stipes of the fruiting bodies were analysed separately. The analyses were carried out by inductively coupled plasma - optical emission spectrometry (ICP-OES). The greatest mean lead concentrations of 1.91 and 1.60 mg kg were determined in caps and stipes of Macrolepiota procera. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
3
18
1
1
Order By: Relevance
“…In general, the pattern of the 210 Pb and 210 Po distribution within the mushrooms seems to be species dependent (Guillén and Baeza 2014 ), e.g., in some species of the Boletaceae family, the cap content was higher than that of the stipe (Vaaramaa et al 2009 ). Similarly, the average concentrations of heavy metals (Ni, Cr, Pb, Cd, and Hg) in the anatomical parts of the fruiting body (cap and stipe) were considerably different (Falandysz et al 2008 ; Baptista et al 2009 ; Širić et al 2017 ; Falandysz et al 2017a ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the pattern of the 210 Pb and 210 Po distribution within the mushrooms seems to be species dependent (Guillén and Baeza 2014 ), e.g., in some species of the Boletaceae family, the cap content was higher than that of the stipe (Vaaramaa et al 2009 ). Similarly, the average concentrations of heavy metals (Ni, Cr, Pb, Cd, and Hg) in the anatomical parts of the fruiting body (cap and stipe) were considerably different (Falandysz et al 2008 ; Baptista et al 2009 ; Širić et al 2017 ; Falandysz et al 2017a ).…”
Section: Resultsmentioning
confidence: 99%
“…Important components of ecosystems in remediation of metals in the environment are plants (Prasad and Freitas, 2003) but also other organisms like mushrooms which are known to accumulate high concentrations of toxic metallic elements and metalloids (Svoboda et al, 2006;Borovicka et al, 2010). Accordingly, Siric et al (2016) and Siric et al (2017) investigated bioaccumulation potential in mushrooms from Croatia and found bioaccumulation ability of Cd and Hg for all examined species. The ability to accumulate heavy metals varies between species and among cultivars within species, based on their genetic, morphological, physiological and anatomical characteristics (Farid et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In combination with their characteristic high bioaccumulative capacity for risk elements (mainly saprophytic fungi) they reduce the content of xenobiotics in other environmental compartments (Árvay et al, 2017;Kojta et al, 2016;Stefanović et al, 2016;Angelovičová and Fazekašová 2014) at the expense of increasing content of the contaminants in their fructification organs (Slávik et al, 2013). Many studies show that the quality of the environment is a significant factor affecting the content of the risk elements in the above-ground parts of mushrooms, as well as plants and/or products (Falandysz 2017;Širić et al, 2017;Stanovič et al, 2016;Mleczek et al, 2015;Árvay et al, 2014;Tomáš et al, 2014;Mleczek et al, 2013). Based on these properties, it can be stated that the wild growing mushrooms are an important bioindicator of environmental pollution Árvay et al, 2012), especially in areas affected by significant industrial activity (Gao and Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%